"The Secret Sauce": Popular Jazz Performances on TikTok. - Burkhart, Benjamin (Popular Music & Society, 2025)
TikTok is a short-form video platform where videos with a typical duration of 15 to 60 seconds are shared. Although it may seem unlikely at first glance, jazz is very popular on the platform. However, only very specific facets of jazz culture achieve high visibility on TikTok. I hypothesize that this is due to certain platform logics of TikTok that influence the production cultures of jazz musicians and encourage the production of specific types of jazz-related content. Based on interviews with popular jazz musicians, I analyze the socio-technical interplay of human and non-human actors on TikTok in the jazz context.